A Development of RFID Based Sales and Inventory System for Hup Seng Aluminium - Lee Hui Lian,; Hannani Aman, (Applied Information Technology And Computer Science, 2022)
Hup Seng Aluminium & Glass is a company that using the aluminium’s raw material that ordered from the supplier to build aluminium product such as door, cupboard, wardrobe, cabinet and window for sales. The problem faced by the company are the administrator uses manual system to record their business operation, difficult to track the inventory of aluminium’s raw materials and products, the manual calculation of sales may occur human’s mistake and the administrator unable to make replenishment of raw materials and products on time. The objectives are to design a Sales and Inventory System for managing the business record using structure approach, to develop the system using waterfall model and to test the system using functional testing. The system acts as a medium to manage inventory of raw materials and products, purchase order, sales order, user and supplier account and sales calculation. The system stores all the information of raw materials and products. The system stores the detail of sales order when customer purchasing and purchase order when ordering raw materials from supplier. Besides, the owner of the company shall receive sales report within given time of period. The administrator able to view the low stock item in dashboard in order to make replenishment immediately to maintain the stock in adequate level. The stock of raw materials will be deducted automatically when a product is added. The stock of raw materials will be added automatically when the purchase order is received while the stock of products will be deducted automatically when the sales order is delivered. Meanwhile, the user able to generate invoice in pdf format, download it and email it. The development of the system helps the company to reduce the problem occur in the business process and manage all business data in an easy way.